E-072 Impact of obesity on short-term in-hospital outcomes in patients undergoing spinal fusion procedures. (22nd July 2019) - Colburn, T; Schirmer, D; Rose-Reneau, Z; Wright, B
Abstract : Background: Spinal fusion is a surgical procedure utilized to treat or alleviate several spinal diagnoses including: tumor, spinal stenosis, degenerative disc disease, scoliosis, and spondylolisthesis. Previous studies have explored clinical outcomes for this intervention. This study aims to further investigate short-term outcomes of patients after spinal fusion by looking at the impact of obesity. Methods: This retrospective cohort study utilized data from the Nationwide Inpatient Sample (NIS) to identify adult patients (18+) from 2012–2015 who underwent spinal fusion. ICD-9 codes identified these patients; specifically patients diagnosed with obesity. Any patients missing important clinical identifiers (age, gender, cause of death) and patients without spinal fusion intervention were excluded. Data analyses assessed hospital length of stay (LOS), inpatient charges, average age of admission and mortality rate. Results: Of the 290, 752 patients that underwent spinal fusion procedures, 374 had the diagnosis of obesity (OB): Mean mortality rate of patients was significantly increased (1.9%, OB vs. 0.6%, no OB p = 0.01) LOS in patients with obesity who underwent spinal fusion was significantly increased (7.02 days, OB vs. 4.02 days, no OB, p = 0.0001) Total hospital charges were significantly increased (142, 853.68, OB vs. 98, 294.43, no OB, p = 0.0001) Age at admission was not significant in patients with obesity (58.43 years, OB vs. 57.69 years, no OB, p =.307) Conclusion: Patients who are obese and undergo a spinal fusion procedure suffer from increased mortality rate, LOS, and total hospital charges. This study aims to provide physicians with information in the management of patients with obesity that undergoes spinal fusion procedures. Peri-procedural patient optimization could provide a potential avenue to lower LOS, total in-hospital charges, and mortality in patients. Disclosures: T. Colburn: None. D. Schirmer: None. Z. Rose-Reneau: None. B. Wright: None.